Budgetary Clientelism and Decentralization in Hungary and Romania. Issue 1 (March 2023) - Gherghina, Sergiu; Volintiru, Clara
The literature on clientelism covers the extent to which public budgets are politicized relative to specific groups of supporters. However, we know little about what drives the discretionary transfers from central to local governments. This article addresses this research gap and analyses the causes for such allocations in two East European countries: Hungary and Romania. The analysis draws on an original dataset that includes the transfers from central to local budgets in 2019 and the political affiliation of local governments. Our findings illustrate that the degree of decentralization and the electoral system can explain this type of clientelism.